Implementing Quizizz as Game Based Learning in the Arabic Classroom - mei, Suo Yan; Ju, Suo Yan; Adam, Zalika (European Journal of Social Science Education and Research, 2020)
Quizizz is an online assessment tool as a fun multiplayer classroom activity that allows all students to practice together with their computer, Smartphone and I Pad. The main purpose of this research is evaluating the effectively interesting of students for Arabic class by implement of Quizizz as a game based learning in the Arabic classroom of Sultan Idris Education University Malaysia . The researchers tested 85 students for 3 sections during Arabic course titled “Arabic skill”. And created 20 questions relevant to the topics which are students already learned before by using Quizizz as games based learning for 20 minutes before finishing Arabic class once the students feel very tired, sleeping and bored for their Arabic class. And a set of questioners was distributed to those students regarding to their opinion of implementing Quizizz during the Arabic class. According to testing the implementing of Quizizz by researcher during the Arabic skill classroom, found that all students were very active to answer the questions which provided by researches, and more concentrated on the topic. And the results of the questioners shows that the students displayed the position attitude for quizizz as a online teaching and assessment tool during the Arabic class.